pH-activated antibiofilm strategies for controlling dental caries - Wang, Xiuqing; Li, Jingling; Zhang, Shujun; Zhou, Wen; Zhang, Linglin; Huang, Xiaojing (Frontiers in Cellular and Infection Microbiology, 2023)
Dental biofilms are highly assembled microbial communities surrounded by an extracellular matrix, which protects the resident microbes. The microbes, including commensal bacteria and opportunistic pathogens, coexist with each other to maintain relative balance under healthy conditions. However, under hostile conditions such as sugar intake and poor oral care, biofilms can generate excessive acids. Prolonged low pH in biofilm increases proportions of acidogenic and aciduric microbes, which breaks the ecological equilibrium and finally causes dental caries. Given the complexity of oral microenvironment, controlling the acidic biofilms using antimicrobials that are activated at low pH could be a desirable approach to control dental caries. Therefore, recent researches have focused on designing novel kinds of pH-activated strategies, including pH-responsive antimicrobial agents and pH-sensitive drug delivery systems. These agents exert antibacterial properties only under low pH conditions, so they are able to disrupt acidic biofilms without breaking the neutral microenvironment and biodiversity in the mouth. The mechanisms of low pH activation are mainly based on protonation and deprotonation reactions, acids labile linkages, and H+-triggered reactive oxygen species production. This review summarized pH-activated antibiofilm strategies to control dental caries, concentrating on their effect, mechanisms of action, and biocompatibility, as well as the limitation of current research and the prospects for future study.